Pengembangan Aplikasi Klasifikasi Gambar Menggunakan Library Tensorflow yang Menerapkan Algoritma Convolutional Neural Network Studi Kasus: Galeri Foto Kegiatan Ibadah Gereja Shoot Fellowship - Willyam Saputra; Yulius Denny Prabowo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This research is aimed to research and develop a desktop application which will classify images of church activities using the Convolutional Neural Network method to group image data so as to facilitate image search. The dataset used in this research is image data of church activities of SHOOT Fellowship. The software development flow used is an incremental model and the user interface will be created using the Tkinter framework.